O corporativismo na (re)organização do Estado-Nação: Oliveira Vianna e Oliveira Salazar - George Freitas Rosa de Araujo (Centre de Recherches sur les Mondes Américains, 2018)
The object of our study concerns corporatist proposals of (re)organization in the Nation-State regarding the thought of two contemporary intellectuals: The Brazilian Francisco José de Oliveira Vianna (1883-1951) and the Portuguese António de Oliveira Salazar (1889-1970). Both acted as interpreters of their respective nations, thinking foundational and propositional aspects to what they considered to be crucial back then. These national-corporatist proposals inextricably correlate state restructuring and labor (re) organization and patron at a time of political and economic liberalism crisis. Given the impact of these guidelines in a national level, these intellectuals have engendered decades of both positive and negative realities in their representative countries. In order to accomplish this work, we pay special attention to the analysis of the primary sources relatively unknown in the Social Sciences.